AB0644 B Cell Characterization in ADA2 Deficiency Patients. (9th June 2015) - Schena, F.; Volpi, S.; Pastorino, C.; Caorsi, R.; Omenetti, A.; Penco, F.; Chiesa, S.; Bertoni, A.; Picco, P.; Aksentijevich, I.; Martini, A.; Traggiai, E.; et al.
Abstract : Background: ADA2 deficiency, a recently described disease, is characterized by systemic vasculopathy and episodes of strokes. The defect is due to a loss of function mutation of CECR1 gene, codifying for Adenosine Deaminase 2 protein. This protein regulates the catabolism of extracellular adenosine, which we have recently shown is an important regulator of Class Switch Recombination in B lymphocytes. Accordingly DADA2 patients can present hypogammaglobulinemia. Objectives: The aim of the project is to characterize peripheral B-cell compartment of two patients to directly address if ADA2 mutation affects B-cell function. Methods: Two brothers (15 and 7 years old) carrying mutations in CECR1 were followed up from the age of two. They showed similar clinical history with livedo reticularis, fever, vasculitis and neurological symptoms caused by haemorragic strokes. Both presented early hypogammaglobulinemia requiring intravenous immunoglobulin replacement therapy. Remarkably after etanercept treatment serum Igs slowly increased to a normal level. We analyzed peripheral B-cell phenotype by flow cytometry, in vitro B-cell proliferation and differentiation to plasmacells in response to CpG, BCR and T cell help. Results: Flow cytometer analysis showed a significative reduction of total B cells compared with age matched controls. Intriguingly a defect in the memory B-cell compartment (CD19 + CD27 + ) was observed. We found that the rate of proliferation and differentiation to Igs secreting cells is lower as compared to normal controls and it is not supported by autologous T cells. Conclusions: Our findings suggest that ADA2 defect could lead to a reduced formation of T cell dependent memory B cells. References: Zhou Q. et al., N Engl J Med. 2014 Mar 6;370(10):911-20 Navon Elkan et al. P. N Engl J Med. 2014 Mar 6;370(10):921-31 Garg N. et al. Eur J Pediatr. 2014 Jun;173(6):827-30 Schena F. et al. Cell Rep. 2013 Jun 27;3(6):1824-31 Hasko G. et al. Trends Mol Med. 2013 Jun;19(6):355-67 Antonioli L. et al. Nat Rev Cancer. 2013 Dec;13(12):842-57 Eltzschig HK et al. N Engl J Med. 2012 Dec 13;367(24):2322-33. Disclosure of Interest: None declared